Analisis Flypaper Effect Pengeluaran Pemerintah Daerah di Provinsi Bengkulu - barika barika (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2020)
In the context of regional autonomy, the source of regional revenue consists of transfers from the central government and regional own-source revenues (PAD). Many studies have identified the Flypaper effect on these two sources of revenue, with local governments generally responding to higher spending on revenues from transfers compared to sources from PAD. This study aims to determine whether the flypaper effect phenomenon is also found in regional government expenditure in Bengkulu Province. The study uses panel data, consisting of 10 districts / cities in Bengkulu province in the period 2011-2016, using the Fix Effect Model analysis technique. The results of the study found that there has been a Flypaper Effect phenomenon in regional spending in Bengkulu Province. It shows that the coefficient value of general allocation funds is greater than the coefficient value of local revenue.